FONTES DE FIBRA FISICAMENTE EFETIVA NA DIETA DE BOVINOS DE CORTE - Marcus Vinicius Garcia Niwa (2022)
The objective of this work was to evaluate the effects of diets with different levels of fiber from forage on the metabolism and performance of finishing beef cattle in feedlot. In the metabolism study, 4 crossbred steers (514 ± 4.54 kg of body weight) castrated and cannulated in the rumen were used, and these were randomly distributed among the experimental treatments in a 4 x 4 Latin square design. The treatments were diets with the following levels of fiber from corn silage: 9.5%, 5.5%, 2.5% and 0.0%. The variables of nutrient intake, apparent digestibility, ruminal parameters, blood parameters and behavioral parameters of confined beef cattle were evaluated. The consumption of DM, MO, PB, EE, FDN, FDN8mm, FDN1.18mm showed a quadratic behavior (P≤0.05). The CP digestibility showed a linear behavior (P≤0.05) and the NDF digestibility showed a quadratic behavior (P≤0.05). Ruminal pH showed a linear behavior (P≤0.05), VFA production (mmol/L) and the proportions of acetate, propionate and butyrate in the rumen fluid showed a quadratic behavior (P≤0.05). Behavioral parameters showed quadratic behavior (P≤0.05) for idle time and rumination. Therefore, diets with forage NDF between 5.5 and 2.5% of DM maximized DMI, however they presented greater rumen challenge in terms of pH. In the performance study, 24 Nellore steers weighing 330 ± 4.54 kg of body weight (BW) were used. The animals were confined in individual pens, and randomly distributed among treatments that were 9.5% diet; 5.5%; 2.5%; and 0.0% NDF from corn silage. The animals were kept in feedlot for 114 days, and throughout this period, nutrient intake, weight gain, feed conversion, carcass and meat characteristics of the animals were evaluated. Quadratic effect was detected for dry matter (DM), crude protein, ether extract, NDF, and effective NDF intake (NDFef8mm and NDFef1.18 mm). Quadratic effect was detected for average daily gain (GMD) and feed conversion (CA). Linear and quadratic effects were not detected for initial weight, final weight, hot carcass weight, carcass yield, internal and external depth, carcass length, pH, subcutaneous fat thickness, ribeye area, and meat color and animal fat. Although forage NDF concentration did not affect carcass characteristics, fat and meat color, levels between 3.85 to 5.10% forage NDF improve the productive performance of confined Nellore steers.